2021
DOI: 10.1007/s40495-021-00259-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytocompounds of Rheum emodi, Thymus serpyllum, and Artemisia annua Inhibit Spike Protein of SARS-CoV-2 Binding to ACE2 Receptor: In Silico Approach

Abstract: , the disease caused by SARS-CoV-2, has been declared as a global pandemic. Traditional medicinal plants have long history to treat viral infections. Our in silico approach suggested that unique phytocompounds such as emodin, thymol and carvacrol, and artemisinin could physically bind SARS-CoV-2 spike glycoproteins (6VXX and 6VYB), SARS-CoV-2 B.1.351 South Africa variant of Spike glycoprotein (7NXA), and even with ACE2 and prevent the SARS-CoV-2 binding to the host ACE2, TMPRSS2 and neutrapilin-1 receptors. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 70 publications
0
36
0
1
Order By: Relevance
“…There were several other residues, namely K342, C437, Q438, D440, T459, S460, G462, G464, A466, P471, and G472, involved in van der Waals interaction with most of the compounds. Previous studies have well documented the contributory role of these active site residues ( Rolta et al, 2021 , Tateyama-Makino et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…There were several other residues, namely K342, C437, Q438, D440, T459, S460, G462, G464, A466, P471, and G472, involved in van der Waals interaction with most of the compounds. Previous studies have well documented the contributory role of these active site residues ( Rolta et al, 2021 , Tateyama-Makino et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…Rolta et al [87] studied the antibacterial and antifungal activities of phytocompounds of Rheum emodin (emodin, rhein-13c6, and chrysophenodimethy ether) by molecular docking and MD simulations and found that phytocompounds of R. emodin exhibited the best interaction with bacterial and fungal targets. Similarly, Rolta et al [71] studied the interactions of phytocompounds with the N-protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 2020, and reported that emodin, aloe-emodin, anthrarufin, alizarine, and dantron phytocompounds efficiently inhibit SARS-CoV-2 N-protein. Salaria et al [88] studied the in vitro and in silico antibacterial and antifungal activities of essential oil, thymol derived from Thymus serpyllum, and validated the docking results via MD simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption, distribution, metabolism, excretion, and toxicity (ADMET) screening was performed to evaluate the absorption, toxicity, and drug-likeness properties of the selected phytocompounds. The 3-D structures of 11 phytocompounds (asiaticoside, betasitosterol, bryophyllin A, madecassoside, Mahanimbine, Pennogenin, Rutin, Solasonine, Solamargine, Withaferin A, and Withanone) were saved in smiles format and uploaded on the SWISSADME (http://www.swissadme.ch/) (Molecular Modeling Group of the SIB (Swiss Institute of Bioinformatics) and PROTOX-II (https://tox-new.charite.de/protox_II/) web servers (Charite University of Medicine, Institute for Physiology, Structural Bioinformatics Group, Berlin, Germany) [69][70][71][72] for ADMET screening. SWISSADME is an online tool used to predict ADME and pharmacokinetic and physicochemical features of a molecule, which are the main determinants for clinical trials.…”
Section: Admet Screening and Toxicity Prediction Of Phytocompoundsmentioning
confidence: 99%
“…In addition, bioinformatics studies such as molecular docking have identified natural products with potential antiviral activity against SARS-CoV-2 by blocking the interaction between the spike protein and the ACE2 receptor. Some of the compounds identified by this strategy are artemisinin and gamma mangostin [ 12 , 13 ]. It is important to note that experimental validation of these data based on bioinformatics models is necessary.…”
Section: Introductionmentioning
confidence: 99%